The Relational Organization of Entrepreneurial Ecosystems - Spigel, Ben (Entrepreneurship Theory and Practice, 2017)
Entrepreneurial ecosystems have emerged as a popular concept to explain the persistence of high–growth entrepreneurship within regions. However, as a theoretical concept ecosystems remain underdeveloped, making it difficult to understand their structure and influence on the entrepreneurship process. The article argues that ecosystems are composed of 10 cultural, social, and material attributes that provide benefits and resources to entrepreneurs and that the relationships between these attributes reproduce the ecosystem. This model is illustrated with case studies of Waterloo, Ontario, and Calgary, Alberta, Canada. The cases demonstrate the variety of different configurations that ecosystems can take.